Estudo da termodifusão e efeitos fototérmicos em nanopartículas metálicas e bimetálicas - Fudimura, Karina Amancio [UNIFESP] (2016)
In this work, iron oxide nanoparticles (NPs) coated with several ligands and bimetallic NPs (Fe and Au) were produced following three methodologies: co-precipitation of iron salts, thermal decomposition of coordination compounds and reverse micelle, in order to observe their photothermal behavior through the Z-Scan technique and as singlet oxygen carriers (1O2). Initially, the surfaces of these NPs were functionalized with hydrophobic ligand, such as oleic acid, to avoid the formation of aggregates during the syntheses and subsequently with hydrophilic molecules such as polyethylene glycol, tetraethylammonium and citrate in order to increase the biocompatibility and stability in aqueous solutions. Moreover, NPs were functionalized with methylene blue allowing the use of this system as carriers of singlet oxygen, since upon light exposure, methylene blue reacts with molecular oxygen, leading to the formation of 1O2. For this purpose, kinetic measurements revealed the generation of 1O2 under irradiation (? = 532 nm or ? = 633 nm), indicating this system as potential 1O2 releasing vehicles. Structural, morphological and magnetic characterization were performed using X-ray diffraction (XRD), infrared (FTIR) and UV-Vis spectroscopy, dynamic light scattering (DLS), transmission electron microscopy (TEM) and magnetization (VSM), indicating the formation of nanostructured spherical materials with superparamagnetic behavior and a core composed of magnetite (Fe3O4). By the Z-Scan technique, it was possible to obtain thermal conductivity values of all samples and Soret coefficient (ST) of samples coated with hydrophobic binders. The results indicated that in aqueous solvents the thermal conductivity depends mainly on the coatings used and the thermodiffusion experiments presented values of ST > 0, showing that the NPs suspended in organic solvents have a thermophobic feature by the application of a heat gradient.